MODERNISASI TRANSPORTASI DI KOTA MALANG 1899-1930 - Hudiyanto, Reza (Jurnal Sejarah dan Budaya, 2009)
Abstract: One of the outstanding sign of modernity that occurred on the eve of tweentieth century was the shifting on transportation mode. The convertion from horsepower to machine gave important impact on city life. This article describes impacts of this new means of transportation to the city space and the inhabitant who live on it. The first result includes transportation comersialisation, the implementation of tax on wagon, car and street. Second outcome was increasing of street accident. One reason is the static perception of the people who ride and walk along the street, eventhough the situation of transportation have changed.